Local food consumption values and attitude formation: the moderating effect of food neophilia and neophobia - Hussain, K. (Emerald Group Holdings Ltd., 2022)
Purpose: The local food tourism in Pakistan is increasing rapidly, and it attracts scholars to determine the factors affecting local food tourists' buying choices. Particularly, the authors aim to investigate the role of food consumption values on predicting domestic tourists' attitude toward local food and its effect on the intention to try local food with the moderating effect of personality traits (neophobia and neophilia). Design/methodology/approach: The authors tested the study model on 250 completed responses from local food tourists. They collected the data from three tourism locations (Islamabad, Rawalpindi and Peshawar) in Pakistan. Their study utilizes the consumption value theory within the limits of Pakistan's local food tourism. Findings: The empirical findings show that consumption values, such as price, emotion, interaction, epistemic value, location value and variety value, effectively explain the domestic tourists' attitude toward local food. The authors further report that food neophilia strengthens the local tourists' positive reception toward the local food. However, food neophobia weakens the direction between local tourists' attitude toward local food and the intention to try local food. Practical implications: This study provides insights pertaining to tourists' local food consumption values (LFCVs) to a local destination owner and marketing manager to strategically work on LFCVs that are crucial for domestic tourists to derive their intention to try local food. Practitioners should work on domestic tourists who possess food neophobia trait and enquire them for their rejection or avoidance of a particular local destination. This will enable practitioners to bring innovation and development in the local destination, which ultimately promote local food tourism. Originality/value: This study is the first to incorporate the variety and local value in tourists' LFCVs to predict local tourists' attitude toward local food. Additionally, the authors contribute to local food tourism by empirically studying the moderating role of personality traits (food neophilia and food neophobia) to examine the direction between local tourists' attitude and intention to local food. Â© 2021, Emerald Publishing Limited.